1993
DOI: 10.1161/01.str.24.12.1817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation times for patients with in-hospital strokes.

Abstract: Background: Each year at least 35 000 people suffer a stroke while hospitalized, but little is known about the clinical characteristics of such patients or how rapidly they are identified and evaluated. With a recent emphasis on the very early treatment of stroke, in-hospital stroke patients may be candidates for some early interventions.Methods: This was a retrospective study using the stroke registries at two academic medical centers. Data were collected about the clinical characteristics of patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 17 publications
3
58
1
1
Order By: Relevance
“…Therefore, patients who are being admitted to a hospital due to diseases other than stroke may have a stroke during their hospitalization (in-hospital stroke; IHS). It is known that IHS accounts for about 6.5-8.7% of the total number of strokes [1,2]. Previous studies have identified patients with IHS from the hospital-based stroke registry [3,4] or have investigated the association of specific procedures or surgeries with risk of stroke [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients who are being admitted to a hospital due to diseases other than stroke may have a stroke during their hospitalization (in-hospital stroke; IHS). It is known that IHS accounts for about 6.5-8.7% of the total number of strokes [1,2]. Previous studies have identified patients with IHS from the hospital-based stroke registry [3,4] or have investigated the association of specific procedures or surgeries with risk of stroke [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, there were substantial delays between symptom recognition, neurological assessment, and i.v. rt-PA treatment when stroke developed during hospitalization [1,29].To speed up the recognition and assessment of IHS patients, education and training are required for nursing staffs and physicians. However, when considering the complexity of practice, diversity of co-morbid diseases, and number of potential trainees to be educated or trained in a hospital, the implementation of an entire hospital-wide activation system for stroke occurrence is presumably difficult or may be ineffective.…”
mentioning
confidence: 99%
“…Most ischemic IHS occur on cardiological or cardiosurgical wards 11 after coronary artery bypass graft (CABG) or percutaneous coronary intervention (PCI) 9,12 or, more generally, after invasive procedures (70%) 13 . Accordingly, most patients with IHS are hospitalized because of myocardial infarction (MI) or CABG 14 .…”
Section: Etiology Risk Factors and Outcomementioning
confidence: 99%
“…Stroke etiology according to TOAST criteria 15 is more often reported to be cardioembolic or undetermined in comparison to COS 12,14 . Inflammation, diabetes, dehydration, hypertension or instable blood-pressure, reduced renal function, reduced left ventricular ejection faction, newly detected atrial fibrillation and previous MI or stroke have been described as independent risk factors for IHS [16][17][18][19][20] .…”
Section: Etiology Risk Factors and Outcomementioning
confidence: 99%
See 1 more Smart Citation